2006
DOI: 10.1186/bcr1408
|View full text |Cite
|
Sign up to set email alerts
|

Dense breast stromal tissue shows greatly increased concentration of breast epithelium but no increase in its proliferative activity

Abstract: Introduction Increased mammographic density is a strong risk factor for breast cancer. The reasons for this are not clear; two obvious possibilities are increased epithelial cell proliferation in mammographically dense areas and increased breast epithelium in women with mammographically dense breasts. We addressed this question by studying the number of epithelial cells in terminal duct lobular units (TDLUs) and in ducts, and their proliferation rates, as they related to local breast densities defined histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 10 publications
4
70
0
Order By: Relevance
“…High levels of the cholesterol metabolite 27-hydroxycholesterol were observed to increase estrogen-dependent breast cancer proliferation (8,9). Interestingly, mammographic density, a strong predictor of breast cancer development, is positively correlated with the number of epithelial cells (10), and mammographic density was recently linked to metabolic syndrome (11).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of the cholesterol metabolite 27-hydroxycholesterol were observed to increase estrogen-dependent breast cancer proliferation (8,9). Interestingly, mammographic density, a strong predictor of breast cancer development, is positively correlated with the number of epithelial cells (10), and mammographic density was recently linked to metabolic syndrome (11).…”
Section: Introductionmentioning
confidence: 99%
“…48 It has also been shown that breasts with high density and those with cancer exhibit similar biological characteristics such as increased concentration of epithelial and stromal cells and collagen. 32,33,51 Epithelial cell proliferation is necessary for breast density increases, however since breast cancer primarily evolve from epithelial cells, increased numbers of epithelial cells in the dense breast increase the possibility of cancer. 33 Stromal cells induce cancer by modulating epithelial cells through epidermal growth factor receptor, IGF-1, and TGF-β.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%
“…32,33,51 Epithelial cell proliferation is necessary for breast density increases, however since breast cancer primarily evolve from epithelial cells, increased numbers of epithelial cells in the dense breast increase the possibility of cancer. 33 Stromal cells induce cancer by modulating epithelial cells through epidermal growth factor receptor, IGF-1, and TGF-β. 52 Stromal cells are also progenitors, of collagen and stromal matrix which promote mammary gland development and tumour invasion [52][53][54] and since collagen is linked to IGF-1 quantities and tumour reorganization, 53 there are increased opportunities for cell proliferation and transformation to cancer.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%
See 2 more Smart Citations